Analyzing Resilience Strategies of Micro Grocery Kiosks in Strengthening Local Economic Stability - Stefanus Tana; Arnoldus Yefrikson; Claudia Anggraini; Elisabeth Marshanda (Yayasan Cerdas Pedia Indonesia, 2026)
Micro, Small, and Medium Enterprises (MSMEs) represent a fundamental pillar of Indonesia's economic stability. This descriptive qualitative study analyzes the operational resilience strategies of